2015
DOI: 10.1002/hrm.21701
|View full text |Cite
|
Sign up to set email alerts
|

“You Can't Do Both—Something Will Give”: Limitations of the Targets Culture in Managing UK Health Care Workforces

Abstract: (2015) '"You can't do both -something will give": limitations of the targets culture in managing UK healthcare workforces.', Human resource management., 54 (5). pp. 773-791. Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 43 publications
(68 reference statements)
1
43
0
1
Order By: Relevance
“…Interestingly, Newton et al, 116 in a study involving 374 acute care nurses, found that nurses often took independent action to address poor care rather than pursue official channels of compliant. McCann et al 111 observed a similar phenomenon, whereby, in response to more challenging performance targets amid a reduction in resources, both front-line and mid-management employees resorted to 'a form of "street-level bureaucracy" -a situation in which traditional professional norms are reasserted informally in ways that often transgress prescribed performance systems'.…”
Section: Professional Standards Including Ethical Codes Of Practice mentioning
confidence: 95%
See 2 more Smart Citations
“…Interestingly, Newton et al, 116 in a study involving 374 acute care nurses, found that nurses often took independent action to address poor care rather than pursue official channels of compliant. McCann et al 111 observed a similar phenomenon, whereby, in response to more challenging performance targets amid a reduction in resources, both front-line and mid-management employees resorted to 'a form of "street-level bureaucracy" -a situation in which traditional professional norms are reasserted informally in ways that often transgress prescribed performance systems'.…”
Section: Professional Standards Including Ethical Codes Of Practice mentioning
confidence: 95%
“…Similarly, there was little attention afforded to potential variations in approaches to whistleblowing between the public, private and voluntary sectors providing health care, with the literature rarely making a distinction between these groups. The evidence from McCann et al 111 highlights the impact of austerity measures in the NHS on whistleblowing, and more specifically on voice: given the difficulties of meeting more challenging targets with fewer resources, the authors report that NHS staff often resort to 'under-the-radar' tactics to deliver the quality of care that they feel meets their professional standards, while avoiding the potential risks associated with 'speaking up'. Set against the backdrop of austerity in the NHS described by Hyde 137 and McCann et al, 111 it can be seen how pressure to meet business targets begins to undermine nurses' confidence in their judgement on what is an acceptable level of care, and thereby modify their behaviours in response.…”
Section: Economic and Financial Influencesmentioning
confidence: 99%
See 1 more Smart Citation
“…gaming, lying) (Carmichael 1970). hospitals, schools, universities) and, when these relations are changed, perverse effects may appear (McCann et al 2015). In some contexts, gaming and low-trust environments are considered a 'price worth paying' (Berliner 1956) or 'part of business life' (Jensen 2003).…”
Section: Explanations Of How and Why Unintended Consequences Occurmentioning
confidence: 99%
“…In the face of increasing financial pressure, there is a need to examine the collective and cultural effects of discursive practices which use cost-effectiveness as a metric for decisions about healthcare provision. As austerity measures constrain the funding available to healthcare organisations, even as demand is rising, something must give 4 and whistleblowers are perhaps the last line of defence in raising the alarm that care quality is at risk.…”
Section: Shaping Ideas About Care Quality and Patient Safetymentioning
confidence: 99%